Pathogenic bacteria target NEDD8-conjugated cullins to hijack host-cell signaling pathways. - Grégory Jubelin (Public Library of Science (PLoS), 2010)
The cycle inhibiting factors (Cif), produced by pathogenic bacteria isolated from vertebrates and invertebrates, belong to a family of molecules called cyclomodulins that interfere with the eukaryotic cell cycle. Cif blocks the cell cycle at both the G₁/S and G₂/M transitions by inducing the stabilization of cyclin-dependent kinase inhibitors p21(waf1) and p27(kip1). Using yeast two-hybrid screens, we identified the ubiquitin-like protein NEDD8 as a target of Cif. Cif co-compartmentalized with NEDD8 in the host cell nucleus and induced accumulation of NEDD8-conjugated cullins. This accumulation occurred early after cell infection and correlated with that of p21 and p27. Co-immunoprecipitation revealed that Cif interacted with cullin-RING ubiquitin ligase complexes (CRLs) through binding with the neddylated forms of cullins 1, 2, 3, 4A and 4B subunits of CRL. Using an in vitro ubiquitylation assay, we demonstrate that Cif directly inhibits the neddylated CUL1-associated ubiquitin ligase activity. Consistent with this inhibition and the interaction of Cif with several neddylated cullins, we further observed that Cif modulates the cellular half-lives of various CRL targets, which might contribute to the pathogenic potential of diverse bacteria.